Zinc, calcium, protein, lead, mercury, and the sensorics quality of cireng snacks supplemented with blood cockle (Anadara granosa) - MARGARETHA SOLANG; DJUNA LAMONDO; SYAM S. KUMAJI (Smujo International, 2017)
Solang M, Lamondo D, Kumaji SS. 2017. Zinc, calcium, protein, lead, mercury, and the sensorics quality of cireng snacks supplemented with blood cockle (Anadara granosa). Nusantara Bioscience 9: 385-391. Blood cockle (Anadara granosa) is a potential nutritious food with high economic value. This study aims at evaluating the level of zinc, calcium, protein, mercury, lead, and the sensorics quality of cireng (traditional Indonesian snack made from fried-tapioca flour dipped into sauces) supplemented with blood cockle. This study used complete randomised design, where the treatment factors consisted of flour made from blood cockles to supplement the flour used in making the cireng snacks. The concentration of the treatment factors were 0%, 5%, 10%, 15%, and 20%. The data were analyzed using the One Way ANOVA test and LSD test. This study shows that blood cockles’ supplementation significantly increases the level of protein (p=0.05), zinc (p=0.031), calcium (p= 0.016), lead (0.000), mercury (p= 0.022) of the cireng snacks. Supplementation of blood cockles has increased the preference toward cireng’s flavor, aroma, and color by 10%, whereas the level of preference toward the texture of cireng which used the blood cockle has increased by 20% compared to cireng product with non-supplemented flour. The level of lead (Pb), and Mercury (Hg) are below the Indonesian National Standard (SNI). Supplementation of blood cockles from Gorontalo in the flour used in making the cireng snacks produced snacks with a better nutrition value and safe to consume. Also, the flavor, color, texture, and aroma are acceptable.